2018
DOI: 10.1002/adtp.201800098
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Cell Homing in Cytotherapeutics and Regenerative Medicine

Abstract: Recent advances in cell science and regenerative therapies mimic the therapeutic effects of patients' own cells when they home to and accumulate at sites of injury. Inspired by stem cell trafficking under in vivo conditions, the facilitation of stem cell homing and the driving of endogenously mobilized mesenchymal stem cells (MSCs) for advanced therapeutics have shown indisputable success in several preclinical studies. In fact, stem cell homing is also relevant for cell transplantation. Ensuring that a suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 211 publications
(197 reference statements)
0
6
0
Order By: Relevance
“…Endeavors aiming to bridge the gap between the promising results obtained with animal models and the reality of clinical treatments indicate that clinical success can be facilitated by avoiding the use of external stem cells. Therefore, studies have established endogenous regenerative techniques involving material design and/or cytokine presentation that permit the patient's own cells to be harnessed for therapeutics . An evolving body of work in this topic corroborates that the recreation of a suitable microenvironment at the injured site can instruct the homing of resident stem cells and can induce the periodontium itself to regenerate.…”
Section: Resultsmentioning
confidence: 99%
“…Endeavors aiming to bridge the gap between the promising results obtained with animal models and the reality of clinical treatments indicate that clinical success can be facilitated by avoiding the use of external stem cells. Therefore, studies have established endogenous regenerative techniques involving material design and/or cytokine presentation that permit the patient's own cells to be harnessed for therapeutics . An evolving body of work in this topic corroborates that the recreation of a suitable microenvironment at the injured site can instruct the homing of resident stem cells and can induce the periodontium itself to regenerate.…”
Section: Resultsmentioning
confidence: 99%
“…QNZ is an inhibitor of the NF-κB signaling pathway [21]. Bone regeneration can be divided into two stages: endogenous stem cell homing to the sites of bone defects and the subsequent osteogenic differentiation of the recruited stem cells [41,42]. In this project, we found that QNZ could rescue BMP2-mediated migration and osteogenic differentiation in MSCs inhibited by fibroblasts.…”
Section: Discussionmentioning
confidence: 85%
“…Cellular homing is the concept of the tight integration of cells to the native tissue through intercellular adhesion [ 31 ]. There were conflicting findings in the ability of MSCs to attach to the affected tissue.…”
Section: Discussionmentioning
confidence: 99%